Evaluation of the digital marketing mix of virtual self-service sales platforms in Colombia (GEON Journal (Management, Organizations and Business), 2020)
This research addresses the evaluation and analysis of the components of the digital marketing mix (product, price, place, promotion and -5P- platform) embodied in the virtual self-service sales platforms in Colombia. In Colombia it is evident the lack of dynamism to take advantage of all the benefits that e-commerce and digital marketing can offer to the companies, which can contribute to their development and growth. This research intends to identify, classify, evaluate and analyze the digital marketing mix of the virtual sales platforms of the self-services existing in Colombia. The research methodology developed is of a quantitative approach, the scope is descriptive, the design is of a non-experimental transversal nature, the technique used is that of content analysis and the instrument for the collection of information is the questionnaire. This research found that the vast majority of virtual sales platforms use various digital marketing tools that create a unique and enjoyable experience for the customer, in line with the theory of this branch of the discipline, in terms of its structure (5 P) and models for evaluating websites. The vast majority of self-service virtual sales platforms in Colombia analyzed present a very pertinent structure in terms of the digital marketing mix and, give an account of the solution to the problems that existed some years ago, making this tool a commercial boost for these companies.JEL Codes: M Business Administration and Business Economics; Marketing; Accounting; Staff economy. M3 Marketing and Advertising. M31 Marketing.
Keywords: Digital marketing; Virtual plataforms; Website Quality